2022
DOI: 10.3389/fimmu.2022.955523
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation syndrome in adults: Characteristics, outcomes, and therapeutic effectiveness of etoposide-based regimen

Abstract: Objectives: To describe the clinical characteristics and outcomes of adult macrophage activation syndrome (MAS) patients and to provide experience for the treatment.Methods: Adult patients with MAS admitted to Beijing Friendship Hospital from December 2014 to September 2021 were enrolled in this study. Clinical data of patients were collected and analyzed.Results: A total of 118 adult MAS patients entered this study. MAS was the first manifestation in 43 (36.4%) patients, while 75 (63.6%) developed MAS after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Some studies have indicated elevated levels of TNF-α-related molecules in MAS secondary to SLE, which can serve as diagnostic markers for the transition from active SLE to MAS [ 31 ]. During the remission phase of MAS, multiple cytokines including TNF-α exhibit decreased levels compared to the active phase [ 32 ]. However, lower levels of TNF-α were found in SLE patients with MAS compared to single SLE patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated elevated levels of TNF-α-related molecules in MAS secondary to SLE, which can serve as diagnostic markers for the transition from active SLE to MAS [ 31 ]. During the remission phase of MAS, multiple cytokines including TNF-α exhibit decreased levels compared to the active phase [ 32 ]. However, lower levels of TNF-α were found in SLE patients with MAS compared to single SLE patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The etoposide (VP-16)-based regimens, a kind of treatment approach for MAS, include HLH-94, HLH-04 and the modified Doxorubicin−Etoposide-Methylprednisolone (DEP) regimen ( 140 ).…”
Section: The Attractive Therapeutic Approach To Prevent Mas In Covid-19mentioning
confidence: 99%
“…found that the use of etoposide can lead to clinical improvement coinciding with a decline of systemic HMGB1, IL-18, IFN-γ, and ferritin levels ( 141 ). Although there is some evidence that this drug may aggravate the infection or make it easier to develop new infections, its benefits are obviously greater ( 140 ).…”
Section: The Attractive Therapeutic Approach To Prevent Mas In Covid-19mentioning
confidence: 99%